The Role of Activating Transcription Factor 3 as a Regulator of DNA-Damaging Chemotherapy Cytotoxicity - Hasim, Mohamed Shaad (Université d'Ottawa / University of Ottawa, 2019)
DNA-damaging chemotherapeutics are a consistently employed for the treatment of cancer, and are regularly part of first-line combination therapeutic regimens. However, these regimens often display limited activity in cancers including of the lung and breast. Novel therapeutic strategies are urgently required. Understanding the molecular mechanisms regulating DNA-damaging chemotherapeutics activity will lead to such novel strategies. Activating transcription factor 3 (ATF3) is a stress inducible gene that plays a significant role in regulating cellular stress including DNA damage. This thesis investigates the role of ATF3 in mediating the cytotoxic effects of two commonly employed DNA-damaging chemotherapeutics, cisplatin and doxorubicin. This study also identifies other independent ATF3 inducing agents in potential novel combination therapeutic strategies. In this study, cell line models of cisplatin-resistance were generated independently from two non-small cell lung cancer (NSCLC) cell lines, Calu6 and H23. Full transcriptome RNA-sequencing analysis identified ATF3 as the most highly dysregulated apoptosis regulatory gene in the cisplatin-resistant compared to their respective parental cell lines following treatment with cisplatin. Further characterization identified cisplatin induced activation of JNK as the key regulator of ATF3 induction in these cell lines. Restoring JNK activity resulted in induced ATF3 expression and re-sensitization of the resistant cell lines to cisplatin treatment. FDA-approved 1200 compound library screens were employed to identify agents that can enhance cisplatin cytotoxicity as well as whose cytotoxicity was dependent on ATF3 expression. Vorinostat, an HDAC inhibitor, was identified in both screens and importantly displayed synergistic cytotoxicity in combination with cisplatin. In addition, ATF3 was also induced with treatments of the DNA damaging agent doxorubicin in these NSCLC cell lines including in the cisplatin resistant models. This work suggested a different mechanism of ATF3 induction by doxorubicin and the potential role of ATF3 in mediating doxorubicin cytotoxicity was further investigated in breast cancer cells. Doxorubicin robustly increased ATF3 expression in human breast cancer cell lines and tumor tissue ex-vivo. Loss of ATF3 in MEFs resulted in reduced sensitivity to doxorubicin treatment compared to wild-type MEFs. Employing the same library screen as above, compounds with ATF3 dependent mechanisms that could enhance doxorubicin cytotoxicity were identified. Vorinostat, as well as, the nucleoside analogues trifluridine and 6-mercaptopurine induced ATF3 expression and enhanced doxorubicin cytotoxicity. This study demonstrated that ATF3 plays an important role in mediating the cytotoxic effect of the DNA-damaging chemotherapeutics cisplatin and doxorubicin. It also provides rationale for ATF3 as a potential therapeutic target, and for the incorporation of ATF3 inducing agents in novel combination therapeutic strategies.
Keywords: Activating Transcription Factor 3; ATF3; Breast Cancer; Lung Cancer; Chemotherapy; Doxorubicin; Cisplatin; Combination Therapy